The impact of celiac disease on the gestational process (Research, Society and Development, 2025)
This article aims to examine how celiac disease affects women of childbearing age, including those who are pregnant or trying to become pregnant, with a focus on obstetric risks, nutritional deficiencies and management approaches. A descriptive bibliographic review, based on articles published between 2015 and 2025 in the PubMed, SciELO, LILACS and Cochrane Library databases. We used the descriptors “celiac disease”, “gestation” and “gluten-free diet” to identify relevant jobs. The results indicate that untreated celiac disease is associated with infertility, spontaneous abortions, premature birth and low birth weight. Furthermore, significant nutritional deficiencies were observed, such as iron deficiency anemia, hypocalcemia and insufficient levels of vitamin D. An analysis demonstrated that a rigorous addition to a gluten-free diet significantly reduces maternal and fetal complications, improving nutritional parameters and obstetric defects. It is concluded that early diagnosis, combined with multidisciplinary support and nutritional education, is crucial to minimize risks and promote healthy pregnancy in celiac patients. It highlights the need for standardized clinical protocols and psychosocial support during the prenatal period, as well as new research to optimize management guidelines.